Critical velocity: A predictor of 2000-m rowing ergometer performance in NCAA D1 female collegiate rowers - Kendall, K. L.; Smith, A. E.; Fukuda, D. H.; Dwyer, T. R.; Stout, J. R. (Journal of Sports Sciences, 2011)
The aims of this study were to examine the use of the critical velocity test as a means of predicting 2000-m rowing ergometer performance in female collegiate rowers, and to study the relationship of selected physiological variables on performance times. Thirty-five female collegiate rowers (mean ± s: age 19.3 ± 1.3 years; height 1.70 ± 0.06 m; weight 69.5 ± 7.2 kg) volunteered to participate in the study. Rowers were divided into two categories based on rowing experience: varsity (more than 1 year collegiate experience) and novice (less than 1 year collegiate experience). All rowers performed two continuous graded maximal oxygen consumption tests (familiarization and baseline) to establish maximal oxygen uptake (VO2max), peak power output, and power output at ventilatory threshold. Rowers then completed a critical velocity test, consisting of four time-trials at various distances (400 m, 600 m, 800 m, and 1000 m) on two separate days, with 15 min rest between trials. Following the critical velocity test, rowers completed a 2000-m time-trial. AbsoluteVO2max was the strongest predictor of 2000-m performance (r = 0.923) in varsity rowers, with significant correlations also observed for peak power output and critical velocity (r = 0.866 and r = 0.856, respectively). In contrast, critical velocity was the strongest predictor of 2000-m performance in novice rowers (r = 0.733), explaining 54% of the variability in performance. These findings suggest the critical velocity test may be more appropriate for evaluating performance in novice rowers.